Development of a Web-based School Information System to Improve Administration and Communication Efficiency - Firmansyah, Taufik; Setiyawan, Muhammad; Turmudi, Hadis (PT FORMOSA CENDEKIA GLOBAL, 2024)
Information technology has brought significant changes in various aspects of life, including in the education sector. This digital transformation has become an important part in driving the progress of a more modern and efficient education. This research developed a web-based school information system to improve the efficiency of administration and communication in schools. This research was conducted in several junior high schools in the Pasarkliwon State Elementary School area, using a qualitative approach and case study design. Data were collected through interviews, observations, and documentation, then analyzed using thematic methods. Results showed that the system significantly improved administrative management, such as student data, grades, and attendance, and improved communication between schools, students, and parents. Challenges faced include lack of staff training and infrastructure limitations. Support through training and infrastructure development is needed for the successful implementation of this system.